Betrayers : a Nameless Detective novel - Pronzini, Bill (Pronzini, Bill. "Nameless Detective" mysteries., 2010)
We're told that there are seven deadly sins; not on the list is the deadliest of them all: Betrayal. For each of the detectives at the agency, a betrayal becomes not only the driving force behind an investigation, but the source of the kind of resolve that cannot be derailed by threats. Tamara's case began as something personal but explodes as her investigation of her former lover leads to a scam that bilks charities in the name of helping the homeless and indigent. For Nameless, trying to find out who is gaslighting an old woman only exposes the ugly side of family. Runyon has a different difficulty: his case of a bail-jumper with some bad family ties is easy enough as these things go, but he's being confronted by a demon that is going to try to force him into a betrayal..